2008
DOI: 10.1152/ajpregu.00708.2007
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol preference in mice lacking the Avpr1a vasopressin receptor

Abstract: [Arg(8)]-vasopressin (Avp), a nonapeptide hormone, is known to regulate blood pressure, water balance, and a variety of behaviors such as anxiety, aggression, and bonding. Although some evidence that Avp modifies ethanol consumption and some of the effects of ethanol on behavior have been reported, the role of Avp in alcohol consumption and preference is poorly understood. The Avp1a receptor (Avpr1a) is ubiquitously expressed in the central nervous system. To determine the role of Avp signaling on the behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 55 publications
(92 reference statements)
1
23
0
Order By: Relevance
“…In the context of ethanol-induced CSP, OXT and AVP have contrasting effects: in male mice, these neuropeptides increase social behavior [1] and modify ethanol consumption [2427]. Nonetheless, the lack of ethanol-induced CSP in KO Oxtr and KO Avpr1a females in the present study was consistent with our hypothesis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the context of ethanol-induced CSP, OXT and AVP have contrasting effects: in male mice, these neuropeptides increase social behavior [1] and modify ethanol consumption [2427]. Nonetheless, the lack of ethanol-induced CSP in KO Oxtr and KO Avpr1a females in the present study was consistent with our hypothesis.…”
Section: Discussionsupporting
confidence: 90%
“…OXT reduces ethanol consumption in wild-type (WT) rats [24] and mice [25]. Reports of ethanol consumption in mice lacking Avpr1a (KO Avpr1a ) are conflicting: one study of males and females found no effect [26], while another reported increased ethanol consumption and preference in males, with limited effects in KO Avpr1a females [27]. Because OXT and AVP enhance social behavior [28] but reduce drug [29, 30] and ethanol consumption [24, 25], we hypothesized that Oxtr and Avpr1a are necessary for conditioned effects of an ethanol-associated social stimulus.…”
Section: 1 Introductionmentioning
confidence: 99%
“…One study found that V1aR-KO mice display increased ethanol consumption and preference (437), but another study found contradictory evidence (83). Also, one study and our unpublished study found that V1bR-KO mice do not show an increase in ethanol consumption and preference (83) (Tanoue et al, unpublished data).…”
Section: Water Intake Food Intake (Appetite) and Alcohol Intake (Prmentioning
confidence: 99%
“…It has been suggested that AVP inhibits the release of glutamate from the presynaptic terminal via the V1a receptor. Blockade of AVP/V1a receptor signaling results in elevation of glutamate levels in the CNS, which accordingly leads to increased ethanol consumption and preference (437).…”
Section: Water Intake Food Intake (Appetite) and Alcohol Intake (Prmentioning
confidence: 99%
“…Further links to social behavior in humans were demonstrated by association of RS1-RS3 haplotypes with the personality trait reward dependence (13), association of RS3 with altruistic behavior (15), and a recent finding of an association between AVPR1A and pair bonding in humans (16). Interestingly, mice lacking AVPR1A display increased ethanol intake (17). …”
mentioning
confidence: 99%